Total parathyroidectomy with forearm auto-transplantation improves the quality of life and reduces the recurrence of secondary hyperparathyroidism in chronic kidney disease patients. Issue 49 (December 2017) - Li, Jia-Gen; Xiao, Zhang-Sheng; Hu, Xian-Jie; Li, Yun; Zhang, Xing; Zhang, Song-Ze; Shan, Ai-Qin
Abstract: Background: Our study aims to explore the effect of total parathyroidectomy (PTX) with forearm autotransplantation (FAT) on the quality of life and recurrence of secondary hyperparathyroidism (SHPT) in chronic kidney disease patients. Methods: A total of 104 chronic kidney disease patients with SHPT were enrolled and divided into the PTX (n = 62) and PTX + FAT (n = 42) groups. The operation efficacy was evaluated by analyzing preoperative and postoperative values, including levels of intact parathyroid hormone (iPTH), serum phosphorus, serum calcium, alkaline phosphatase (ALP), calcium-phosphorus product, signs and symptoms, and MOS 36-item short-form health survey (SF-36) scores. Moreover, complications and recurrences were followed up for 12 months after the operation. Binary logistic regression was to present the risk factors for the recurrence of chronic kidney disease patients with SHPT. Results: Compared with the preoperative values, the PTX and PTX + FAT groups showed decrease postoperative levels of iPTH, serum phosphorus, serum calcium, calcium-phosphorus product, bone pain, and skin pruritus at all time periods. The PTX and PTX + FAT groups demonstrated decreased ALP, fracture or deformity, and coronary artery calcification at 1 month, decreased short stature at 3 months after the operation but increased SF-36 score after operation. Compared with the PTX group, the level of iPTH decreased and the levels of serum calcium, calcium-phosphorus product increased at 3, 6, and 12 months after the operation in the PTX + FAT group. The levels of ALP, fracture or deformity, short stature, and SF-36 decreased separately at 1 week and 6 and 12 months after the operation, along with the decrease of coronary artery calcification and the recurrence rate, respectively, at 6 and 12 months after the operation in the PTX + FAT group when compared with those in the PTX group. Logistic regression analysis evidenced that the preoperative iPTH level, SF-36 score, and operation type were the risk factors for the recurrence of chronic kidney disease with SHPT. Conclusion: Total PTX combined with FAT is more effective in improving the quality of life and reducing the recurrence of chronic kidney disease with SHPT than PTX alone.